Challenges of rock drilling and opportunities from bio-boring - Yumeng Zhao; Sheng Dai (Biogeotechnics)
Drilling plays a significant role in the history of human civilization. The exploration of greater depths, extreme environments, or hazardous areas calls for more energy-efficient and high levels of autonomous drilling technologies with reduced cost and improved safety. Meanwhile, nature presents numerous biological boring examples that can be a source of inspiration to renovate our current drilling technologies. This paper reviews both man-made and biological drilling strategies and quantifies their performance by the dimensionless specific drilling energy and the rate of penetration. The results highlight that rotary drilling (including tunnel boring machines) remains the most popular method for subsurface drilling due to its advanced technical status and fewer environmental concerns. For harder rocks, the specific energy of rotary drilling increases dramatically, while percussion drilling requires nearly the same if not lower specific energy but with compromised bit durability that can significantly slow down the drilling operation. Innovative drilling technologies developed and tested in the laboratory still demand improved energy efficiency and penetration rate to be competitive. Bio-boring by natural organisms mostly outperforms man-made drilling technologies in terms of energy efficiency, penetration rate, or both. Studying the underlying mechanisms of bio-boring and translating such knowledge into developing innovative drilling technologies are of significance to subsurface construction and exploration.